2011
DOI: 10.1200/jco.2010.31.8311
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Cancers After an Index Head and Neck Cancer: Subsite-Specific Trends in the Era of Human Papillomavirus–Associated Oropharyngeal Cancer

Abstract: In patients with HNSCC, the risk and distribution of SPM differ significantly according to subsite of the index cancer. Before the 1990s, hypopharynx and oropharynx cancers carried the highest excess risk of SPM. Since then, during the HPV era, SPM risk associated with oropharyngeal SCC has declined to the lowest risk level of any subsite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
301
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(316 citation statements)
references
References 38 publications
13
301
1
1
Order By: Relevance
“…[32,33] According to the literature, the incidence of second primary malignancy in larynx cancers ranges between 11-29%. [34][35][36] In a populationbased study performed between 1986-2008, Liao et al determined that 9,996 patients out of 93,891 patients with head neck cancer (11%) had second primary malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…[32,33] According to the literature, the incidence of second primary malignancy in larynx cancers ranges between 11-29%. [34][35][36] In a populationbased study performed between 1986-2008, Liao et al determined that 9,996 patients out of 93,891 patients with head neck cancer (11%) had second primary malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, other authors reported a lower risk of SPT in HPV-positive oropharyngeal SCC, emphasizing that this fact may be a major contributor to the demonstrated superior survival outcomes among patients with HPV-positive disease. 18 The presence of HPV was detected in the esophageal mucosa of our patient, but the oral lesion was HPV-negative. As the development of SCC remains not totally understood, mainly in patients that lack the habit of tobacco and alcohol, modern molecular techniques may elucidate overall understanding of the biology of these tumors and ways to devise therapeutic strategies to best manage these lesions and improve prospects for survival.…”
Section: Discussionmentioning
confidence: 52%
“…Successful re-challenge of bevacizumab has also been reported but should be done under close supervision, and appropriate BP control should be ensured [20]. The median time to recovery of the neurological symptoms is 7.5 days [21].…”
Section: Discussionmentioning
confidence: 99%